2009
DOI: 10.1177/194008290900200303
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Knowledge of Shade-Coffee Farmers Towards Vertebrates and Their Ecological Functions

Abstract: The purpose of this study was to assess farmers' attitudes, as well as perceptions and knowledge that shape those attitudes, toward the ecological role of vertebrates inhabiting shaded-coffee farms. We also aimed to determine whether differences existed among two groups of farmers: one that had attended environmental education workshops, and one that had not. We conducted 36 oral interviews of farmers in the region of Cuetzalan, Mexico. All farmers were members of an important regional cooperative, Tosepan Tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
3
15
0
2
Order By: Relevance
“…Thus, in a region where the daily wage averages US$12, the use of turtles as a food source has become almost inaccessible. When we compared people exposed and not exposed to TCMIs, we found that people who had not participated in one maintained more utilitarian attitudes toward turtle species, consistent with other studies (Lo´pez-del-toro, Andresen, Barraza, & Estrada, 2009). We found significant differences between the two groups in terms of consumption rates for the focal turtle species but not in terms of rates of exploitation of nonfocal turtle species (with both groups similar in terms of rates of hunting, purchasing, and selling these alternative turtle species).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, in a region where the daily wage averages US$12, the use of turtles as a food source has become almost inaccessible. When we compared people exposed and not exposed to TCMIs, we found that people who had not participated in one maintained more utilitarian attitudes toward turtle species, consistent with other studies (Lo´pez-del-toro, Andresen, Barraza, & Estrada, 2009). We found significant differences between the two groups in terms of consumption rates for the focal turtle species but not in terms of rates of exploitation of nonfocal turtle species (with both groups similar in terms of rates of hunting, purchasing, and selling these alternative turtle species).…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study indicate that the birds which have aesthetic qualities or which are regarded as omens are most commonly recognized by local people, although the results were not significantly different across the three sites. This result is consistent with those reported by Lopez-del-Toro et al (2009) in Mexico, where the farmers of shade coffee plantations also revealed such attitudes towards birds. Similar observations were reported in published studies such as Mokuku and Mokuku (2004), Herold (2005), Kaltenborn et al (2006) and Owusu (2008).…”
Section: Birdssupporting
confidence: 93%
“…Small-scale coffee farmers have sophisticated ecological knowledge about many processes occurring in their farms Perfecto 2013, Valencia et al 2015), but as the literature reports and our preworkshop survey confirms, they know their shade-coffee farms thrive with life but pay little attention to many organisms unless their harm is significant (Segura 2004, Jarquín 2005, 2006, López-del-Toro et al 2009); they are rarely aware that some pesky organisms (e.g., ants and scales) and their inconspicuous ecological associates indirectly exert potential autonomous control over rust and other coffee pests (Perfecto and Vandermeer 2015). Furthermore, they generally lack a framework for learning about subtle ecological processes that would improve pest control at broad spatial and temporal scales (Rebaudo and Dangles 2015).…”
Section: Discussionmentioning
confidence: 80%